Genetic analysis of RNA polymerase-promoter interaction during sporulation in bacillus subtilis. - Ray, C (1987)
The discovery of secondary sigma factors in Bacillus subtilis that enable RNA polymerase to transcribe cloned sporulation genes in vitro has led to the proposal that the appearance of new sigma factors during sporulation directs RNA polymerase to the different temporal classes of sporulation genes. One sigma factor, which appears 2 h after the initiation of sporulation, is sigma E (formerly sigma 29). Mutations that inactivate the structural gene for sigma E prevent transcription from promoter G4. To determine whether sigma E-RNA polymerase interacts with the G4 promoter in vivo, we examined the effects of six single-base-pair substitutions in the G4 promoter on its utilization in vivo and in vitro by sigma E-RNA polymerase. The mutations in the G4 promoter affected utilization of the promoter in vivo in the same way that they affected its utilization in vitro by purified sigma E-RNA polymerase; therefore, we conclude that this polymerase interacts directly with the G4 promoter in vivo. The effects of these mutations also support the model in which sigma E-RNA polymerase utilizes promoters by interacting with two distinct sets of nucleotides located 10 and 35 base pairs upstream from the start point of transcription.